Znikający punkt zwrotny. Piotra Chmielowskiego kłopoty z periodyzacją „najnowszej literatury polskiej” - Wedeman, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
[An outline of the literature of the last sixteen years] written by Piotr Chmielowski was designed in the author’s intention as a sketch of “rather journalistic than historical features”. The above is clearly indicated by the forewords written by the author to its successive four editions published between 1881 and 1898. Still, despite its lack of pretentions, the book acquired with time the status of a fully-fledged instructive approach to Polish literature of the Positivist period. A closer look at the text with regard to the proposed periodization reveals, however, a number of flaws and aporias committed by Chmielowski, particularly in establishing boundary dates of the proposed literary period. The present article attempts to prove that the source for the inaccuracies and inconsistencies of the solutions proposed in Zarys is not so much in their makeshift or the pro tem nature, but rather in the aggressively promoted ideology, represented by Chmielowski, that completely disregarded the nature of literary phenomena.